Types and Syntactical Analysis of Interrogative Sentences Found in Encanto Movie - Ni Nyoman Melinovianti; Ni Putu Cahyani Putri Utami (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
The study focuses on interrogative sentence types and their syntactical analysis in the Encanto movie. The aims of this study are to find the types of interrogative sentences and to analyse sentence structure of interrogative sentences in the Encanto movie. The methods used to analyse the data are observation and qualitative methods. The main theory proposed by Cowan (2008) about interrogative sentences, and the supporting theory proposed by Brown and Miller (1991) about sentence structures. The results obtained are 123 data found consisting of three types of interrogative sentences, those are yes/no questions with a total data of 47 or 38,2% with each positive category yes/no questions containing 22 data, elliptical yes/no questions 4 data and declarative yes/no questions having 21 data which both types were included in the reduced yes/no questions. Then, there are 4 data or 3,3% from tag questions in the category opposite polarity questions. The last, there are wh-questions with total data of 72 or 58,5%. This study expects to contribute insight into interrogative sentences and their sentence structures, and helps students to learn syntax.